ALIH KODE DAN CAMPUR KODE DALAM TRANSAKSI JUAL BELI DI PASAR TRADISIONAL TOHO - Yuliani, Inri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to describe the code switching and code mixing contained in buying and selling transactions in the Toho Traditional Market, based on the type and cause of their occurrence. The benefit of this research is to add insight into code switching and code mixing in buying and selling transactions at the Toho Traditional Market. The method used in this research is descriptive method. The form of this research is a form of qualitative research. Collecting data in this study using tapping techniques and recording techniques, and observation technique. Wiretapping is done with the help of a recording device in the form of a cellphone. Techniques to test the validity of the data in this study are observation persistence, triangulation, and peer discussion. Based on the analysis of the research data, it concludes that there are 24 types of code switching data in the form of. 17 internal data or internal code switching. It is divided into two namely 12 permanent code switching and 5 temporary code switching. 7 data code mixing into or inner code mixing 7 is divided into 5 forms of words, and 2 in the form of phrases. The factors that cause code switching are 11 speaker data factors, and 5 listener or speech partner data factors. Factors that cause code mixing occur, namely there are 5 factors of temporary personal and speaker data, and 2 factors of environmental data or ongoing interactions.